2004
DOI: 10.1161/01.cir.0000145541.63406.ba
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass in Relation to Genetic Variation in Angiotensin II Receptors, Renin System Genes, and Sodium Excretion

Abstract: Background-In the European Project On Genes in Hypertension (EPOGH), we investigated in 3 populations to whatextent left ventricular mass (LVM) was associated with genetic variation in the angiotensin II receptors type 1 (AGTR1 A1166C) and type 2 (AGTR2 G1675A) while accounting for possible gene-gene interactions with the angiotensinconverting enzyme (ACE D/I) and angiotensinogen (AGT Ϫ532C/T) polymorphisms. Methods and Results-We randomly recruited 221 nuclear families (384 parents, 431 offspring) in Cracow (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 31 publications
3
57
0
1
Order By: Relevance
“…Our statistical methods also included single and multiple linear regressions. We included in our models covariables with known physiological relevance 12,20 for left ventricular structure. We additionally searched for possible covariables, using stepwise multiple regressions with the probability value for independent variables to enter and stay in the model set at 0.15.…”
Section: Methodsmentioning
confidence: 99%
“…Our statistical methods also included single and multiple linear regressions. We included in our models covariables with known physiological relevance 12,20 for left ventricular structure. We additionally searched for possible covariables, using stepwise multiple regressions with the probability value for independent variables to enter and stay in the model set at 0.15.…”
Section: Methodsmentioning
confidence: 99%
“…In seven European countries, investigators randomly enrolled nuclear and extended families of White Caucasian ethnicity. Four centers took part in the substudy on echocardiography 10,11 and together enrolled 1522 subjects in Kraków (Poland; n¼325), Novosibirsk (Russian Federation; n¼301), Mirano (Italy; n¼345) and Hechtel-Eksel (Belgium; n¼551). The overall response rate was 67.8%.…”
Section: Study Populationmentioning
confidence: 99%
“…10,11 With subjects in left decubitus and breathing normally, the observers obtained Mmode echocardiograms of the left ventricle from the parasternal long-axis view under control of the two-dimensional image. They positioned the ultrasound beam just below the mitral valve at the level of the posterior chordae tendineae.…”
Section: Echocardiographic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…L191L is a synonymous base substitution in exon5 and Zhu et al ( 2003) found that it was associated with EH in AAs. A few studies assessed the association of A1166C with LVM, with negative findings in white subjects (Castellano et al, 1996;Kuznetsova et al, 2004).…”
Section: Effects Of Angiotensinogen and Angiotensin II Type I Receptomentioning
confidence: 99%